Hubungan Antara Konsep Diri dengan Optimisme Pada Remaja di Pengungsian Korban Erupsi Gunung Sinabung - Rismawati Munthe (Medan State University, 2022)
This study aims to determine the relationship between self-concept in adolescents optimism in the evacuation of victims eruption of Mount Sinabung. The research subject were teenagers who were in the refugee victimsof Sinabung eruption that totaled 80 people. The measuring instruments used is a Likert scale that consist of 46 items of self-concept (α = 0,963 ) and 42 items optimism (α = 0,970 ). Data analysis using techniques r Product Moment. Based on the analysis of data, found that the hypothesis proposed in this study received, that there is a relationship between self – concept in adolescents optimism in the evacuation of victims eruption of Mount Sinabung. This is evidenced by the value or coefficient of correlation ( rxy = 0,844 with p = 0,04 ; p < 0,05). Furthermore as seen from the calculation of the mean hypothetical and empirical mean as well as standard deviation is known that self- concept and optimism adolescents in the evacuation victims Sinabung eruption is low where the average empirical value is lower than the average value of the hypothetical.